ANALISIS PENDIDIKAN PESANTREN TERHADAP AKHLAK SANTRI DI MASYARAKAT - Imam Tazali (Jurnal At-Tabayyun, 2020)
Education is one of the factors that are very decisive and affect social change. Through education is expected to produce the next generation who have a solid ruster to receive the baton of a nation. Education has a role in education in one country especially among teenagers who are experiencing changes in themselves. With pesantren education is able to handle the problem of adolescent akhalq although not whole but can reduce the problems that are being hit in one country. Many education experts worry about uncontrolled education among adolescents with external and internal factors. External factors one of them that occurs and is very influential is Handpone which can be opened sites that are not educational and internal factors there is a lack of parental attention to their children.